2020
DOI: 10.3390/cells9040796
|View full text |Cite
|
Sign up to set email alerts
|

The Brain–Skin Connection and the Pathogenesis of Psoriasis: A Review with a Focus on the Serotonergic System

Abstract: Psoriasis is a common non-communicable chronic immune-mediated skin disease, affecting approximately 125 million people in the world. Its pathogenesis results from a combination of genetic and environmental factors. The pathogenesis of psoriasis seems to be driven by the interaction between innate immune cells, adaptive immune cells and keratinocytes, in a process mediated by cytokines (including interleukins (IL)-6, IL-17 and IL-22, interferon and tumor necrosis factor) and other signaling molecules. This lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 139 publications
(283 reference statements)
0
26
0
2
Order By: Relevance
“…The results showed that 398 overlapping gene targets were obtained through PPI analysis, such as IL6, TNF, IL10 and other immune-related in ammatory factors. Many previous studies have shown that psoriasis is an immune-related disease based on T lymphocytes, which is mainly manifested in the imbalance of the balance between different cytokines and the imbalance of complex interactions in tissue disease [33]. It is well known that the in ammatory state associated with hepatitis C virus infection not only affects the liver, but also affects the entire complicated body system [34].…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that 398 overlapping gene targets were obtained through PPI analysis, such as IL6, TNF, IL10 and other immune-related in ammatory factors. Many previous studies have shown that psoriasis is an immune-related disease based on T lymphocytes, which is mainly manifested in the imbalance of the balance between different cytokines and the imbalance of complex interactions in tissue disease [33]. It is well known that the in ammatory state associated with hepatitis C virus infection not only affects the liver, but also affects the entire complicated body system [34].…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that 398 overlapping gene targets were obtained through PPI analysis, such as IL6, TNF, IL10 and other immune-related inflammatory factors. Many previous studies have shown that psoriasis is an immune-related disease based on T lymphocytes, which is mainly manifested in the imbalance of the balance between different cytokines and the imbalance of complex interactions in tissue disease [ 33 ]. It is well known that the inflammatory state associated with hepatitis C virus infection not only affects the liver, but also affects the entire complicated body system [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…The ‘skin-brain axis’ communication network has been recognized as a mechanism by which the central nervous system (CNS) response to psychological stress results in an afferent relay and physiological outcome in the skin ( Paus et al., 2006 ; Pavlovic et al., 2008 ; Martins et al., 2020 ; Rodriguez-Vallecillo and Woodbury-Farina, 2014 ; Chapman and Moynihan, 2009 ). Stress, through a CNS-mediated mechanism, has been shown to exacerbate peripheral cutaneous manifestations of atopic dermatitis, psoriasis, and even hair growth ( Martins et al., 2020 ; Alexopoulos and Chrousos, 2016 ; Ayasse et al., 2020 ; Paus, 2016 ; Pondeljak and Lugović-Mihić, 2020 ; Theoharides, 2020 ; Torales et al., 2020 ; Yang and Zheng, 2020 ; Zeiser et al., 2021 ). However, in addition to the skin being a target for stress responses, bi-directional signaling is described wherein the skin itself, through the localized production of neuroimmunomodulators and stress catecholamines, can initiate stress signaling to the brain ( Paus et al., 2006 ; Chen and Lyga, 2014 ).…”
Section: Introductionmentioning
confidence: 99%